Scientists’ warning on genetic pollution - Anagnostis Theodoropoulos; Kathryn A. Stewart; Ben Wielstra (Discover Conservation)
Abstract Genetic pollution (i.e. anthropogenic hybridization) is insidious; it is a worryingly common problem that should be taken more seriously. Advances in DNA sequencing technologies make it possible to obtain the information to make management decisions. Yet, policy uptake is urgently needed.